Controlled self-assemblies of polystyrene-block-polydimethylsiloxane micelles in cylindrical confinement through a micelle solution wetting method and Rayleigh-instability-driven transformation. Issue 32 (12th July 2017) - Ko, Hao-Wen; Higuchi, Takeshi; Chang, Chun-Wei; Cheng, Ming-Hsiang; Isono, Komei; Chi, Mu-Huan; Jinnai, Hiroshi; Chen, Jiun-Tai
Abstract : We develop a novel route for the fabrication of polystyrene- block -polydimethylsiloxane micelle nanostructures using anodic aluminum oxide templates. Abstract : Block copolymer micelles have been extensively discussed for many decades because of their applications, such as lithography and drug delivery. However, controlling the morphologies of nanostructure assembly using block copolymer micelles as building elements remains a great challenge. In this work, we developed a novel route to induce micelle assembly in confined geometries. Polystyrene- block -polydimethylsiloxane (PS- b -PDMS) micelle solutions were used to prepare micelle nanostructures, and the critical parameters affecting the morphologies were determined. Micelle nanorods, micelle nanospheres, and multi-component nanopeapods were prepared by wetting anodic aluminum oxide (AAO) templates with micelle solutions. Rayleigh-instability-driven transformation was discovered to play an important role in controlling the morphologies of the micelle nanostructures. This study not only proposes a versatile approach to preparing block copolymer micelle nanostructures, but it also provides deeper insight into the controlling factors of block copolymer micelle morphologies in cylindrical confinement.